Inverted Race Tube Assay for Circadian Clock Studies of the Neurospora Accessions - Sohyun Park; Kwangwon Lee (Fungal Genetics Reports, 2004)
Although the Neurospora crassa circadian clock has been studied for forty years, population studies of natural accessions have been limited by technical difficulties associated with the conventional race tube assay (CRTA) that is used to measure asexual development (conidiation). Due to the buildup of CO2 in the CRTA that represses banding, a mutant strain band (bd) has been utilized for increased visualization of the banding phenotype. In order to study the circadian clock in natural accessions of Neurospora multiple techniques have been explored. One such technique, the rubidium chloride-supplemented race tube assay (RRTA) has been used successfully. Here we present a new technique, the Inverted Race Tube Assay (IRTA) that is a simple modification of the CRTA. We analyzed 5 natural accessions of Neurospora using CRTA, IRTA and RRTA and discuss the advantages of the IRTA in natural variation studies in Neurospora.